INSTITUTIONAL CAPACITY OF THE CUSTOMS SERVICE OF UKRAINE: LAW ENFORCEMENT ASPECT - KHOMA, Valeriy; ZAIATS, Victor (Scientific journal «World of Finance», 2020)
Introduction. The purpose of the customs authorities is to effectively protect society and ensure that appropriate taxes are levied, using, inter alia, the fight against cross-border crime. The way in which the customs carries out its law enforcement mission in combating the above offenses remains in the focus of discussions of the customs administrations – members of the World Customs Organization (hereinafter – WCO), of which Ukraine has been a member since 1992. As a result, there is a growing need for further customs enforcement research and improved, with the support of the WCO Secretariat, exchange of experience and a common approach that will allow customs administrations around the world to unify the methodology they use to identify and mitigate potential institutional risks.The purpose. The article covers the analysis of Ukraine’s own customs service methods and, possibly, taking measures to improve the existing national system, in particular, expanding its legal foundation (assistance to authority) and operational capabilities (options) on which state procedures and practices are based.Methods. In the course of the research, general scientific methods were used, in particular: analysis to determine the content of law enforcement powers of the Customs Service of Ukraine; comparison for the provisions of Ukrainian and international legislation regarding the institutional preconditions for law enforcement activities by national customs services. The synthesis method was used to formulate proposals on the need to improve the customs legislation of Ukraine.Results. The main scientific result of the article is to identify, related to the of customs affairs, shortcomings in the institutional capacity in the field of law enforcement of the Customs Service of Ukraine and determine the prospects for their further elimination. Particular attention is paid to the need to synchronize the provisions of Ukrainian legislation, both among themselves and with the relevant rules in force for Ukraine on customs matters, international agreements.Perspectives. Further research in this direction should be conducted on the basis of the formed theoretical justification of the law enforcement powers of the Customs Service of Ukraine, taking into account the levels of official interaction – departmental, interagency, international.